Impurity scattering effect on charge transport in high-Tc cuprate junctions: Сверхпроводимость и мезоскопические структуры - Tanaka, Y.; Asano, Y.; Kashiwaya, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
It is known that the zero-bias conductance peak (ZBCP) is expected in tunneling spectra of normal-metal/high-Tc cuprate junctions because of the formation of the midgap Andreev resonant states (MARS) at junction interfaces. In the present review, we report the recent theoretical study of impurity scattering effects on the tunneling spectroscopy. In the former part of the present paper, we discuss impurity effects in normal metal. We calculate tunneling conductance for diffusive normal metal (DN)/high Tc cuprate junctions based on the Keldysh Green’s function technique. Besides the ZBCP due to the MARS, we can expect ZBCP caused by the different origin, i.e., the coherent Andreev reflection (CAR) assisted by the proximity effect in DN. Their relative importance depends on the angle a between the interface normal and the crystal axis of high-Tc superconductors. At a = 0, we find the ZBCP by the CAR for low transparent junctions with small Thouless energies in DN; this is similar to the case of diffusive normal metal/insulator/s-wave superconductor junctions. Under increase of a from zero to p/4, the contribution of MARS to ZBCP becomes more prominent and the effect of the CAR is gradually suppressed. Such complex spectral features would be observable in conductance spectra of high-Tc junctions at very low temperatures. In the latter part of our paper, we study impurity effects in superconductors. We consider impurities near the junction interface on the superconductor side. The conductance is calculated from the Andreev and the normal reflection coefficients which are estimated by using the single-site approximation in an analytic calculation and by the recursive Green function method in a numerical simulation. We find splitting of the ZBCP in the presence of the time reversal symmetry. Thus the zero-field splitting of ZBCP in the experiment does not perfectly prove an existence of broken time reversal symmetry state.